2019
DOI: 10.1021/acs.molpharmaceut.8b01333
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ferroquine on the Solubilization of Artefenomel (OZ439) during in Vitro Lipolysis in Milk and Implications for Oral Combination Therapy for Malaria

Abstract: Milk is an attractive lipid-based formulation for the delivery of poorly water-soluble drugs to pediatric populations. We recently observed that solubilization of artefenomel (OZ439) during in vitro intestinal lipolysis was driven by digestion of triglycerides in full-cream bovine milk, reflecting the ability of milk to act as an enabling formulation in the clinic. However, when OZ439 was co-administered with a second antimalarial drug, ferroquine (FQ) the exposure of OZ439 was reduced. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 29 publications
1
38
0
Order By: Relevance
“…A new fixed-dose combination of ferroquine (IND 115 244) and artefenomel (IND 104 549), which have different mechanisms of action, was developed by Sanofi in partnership with Medicines for Malaria Venture (MMV) for the single-dose treatment of uncomplicated malaria in adults and children. Artefenomel, previously known as OZ439, is a synthetic trioxolane endoperoxidic anti-malarial agent [ 26 , 27 ] which, like artemisinins, has multiple mechanisms of action including reacting with iron within the parasite food vacuole to produce free radicals, leading to alkylation of key parasitic proteins [ 26 , 28 , 29 ]. Artefenomel was selected for development based on improved blood stability and an extended plasma half-life relative to artemisinins in rat [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A new fixed-dose combination of ferroquine (IND 115 244) and artefenomel (IND 104 549), which have different mechanisms of action, was developed by Sanofi in partnership with Medicines for Malaria Venture (MMV) for the single-dose treatment of uncomplicated malaria in adults and children. Artefenomel, previously known as OZ439, is a synthetic trioxolane endoperoxidic anti-malarial agent [ 26 , 27 ] which, like artemisinins, has multiple mechanisms of action including reacting with iron within the parasite food vacuole to produce free radicals, leading to alkylation of key parasitic proteins [ 26 , 28 , 29 ]. Artefenomel was selected for development based on improved blood stability and an extended plasma half-life relative to artemisinins in rat [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ferroquine is a ferrocenyl derivative of chloroquine that is active against chloroquine-resistant P. falciparum strains with a promising anti-malarial therapeutic potential in humans [ 31 , 32 ]. It has been proposed to act by preventing haemozoin formation generating reactive oxygen species and inducing lipid peroxidation [ 29 , 31 ]. Ferroquine is metabolized to one major metabolite (N-demethyl derivative, SSR97213), equally active in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…For weakly basic drugs the formation of fatty acids during digestion can be crucial in driving the solubilisation of drug through formation of lipophilic ion pairs [ 57 ]. The solubilisation of solid crystalline drug during digestion has been shown for pharmaceutical lipids [ 71 ], milk [ 57 , 67 , 72 ] and infant formula [ 73 ]. Halofantrine as a model drug was shown to be fully solubilised into full cream milk during digestion but not lower fat milk or casein solutions ( Figure 5 ) [ 57 ].…”
Section: Drug Solubilisation and Crystallisation During Digestion Of Lipid Systemsmentioning
confidence: 99%
“…In the case of artefenomel introduced in the previous section, the digestion of milk lipids led to the rapid solubilisation of artefenomel FB 1, which subsequently reprecipitated as the FB 2 polymorph ( Figure 6 , left panel). Full digestion of the milk lipids did not enable complete solubilisation of artefenomel FB 2 and co-formulation with ferroquine reduced the solubilisation of FB form 2 [ 72 ]. Importantly, subsequent studies showed that the selection of an infant formula with an optimal lipid composition and lipid:drug ratio enabled full solubilisation of artefenomel during digestion ( Figure 6 , right panel) [ 73 ].…”
Section: Drug Solubilisation and Crystallisation During Digestion Of Lipid Systemsmentioning
confidence: 99%
See 1 more Smart Citation